Cancer organoid co-culture model system: Novel approach to guide precision medicine - Yuan, Jin; Li, Xiaoyang; Yu, Shengji (Frontiers in Immunology, 2023)
The three-dimensional cancer organoids derived from self-organizing cancer stem are ex vivo miniatures of a tumor that faithfully recapitulate its structure, distinctive cancer features, and genetic signature. As novel tools, current cancer organoids have been well-established and rapidly applied in drug testing, genome editing, and transplantation with an ultimate aim to enter clinical practice for guiding personalized therapy. However, given that the lack of tumor microenvironment, including immune cells and fibrous cells, is a major limitation of this emerging methodology, co-culture models inspire high hopes for further application of this technology in cancer research. Co-culture of cancer organoids and immune cells or fibroblasts are available for investigating tumor microenvironment, molecular interactions, and even chimeric antigen receptor-engineered lymphocytes in treating cancer. In light of recent progress on cancer organoid co-culture models, it is only apt that we recognize the advantages and drawbacks of this novel model to exploit its full potential. In this review, we summarize the recent advances in the application of cancer organoids and the co-culture model and how they could be improved in the future to benefit cancer research, especially precision medicine.